Bilateral Maxillary Dentigerous Cysts in a Nonsyndromic Child: A Rare Presentation and Review of the Literature - Rakshit Vijay Khandeparker; Purva Vijay Khandeparker; Anirudha Virginkar; Kiran Savant (Case Reports in Dentistry)
Dentigerous cysts represent the second most common odontogenic cysts of the jaws after radicular cysts and are usually associated with the crowns of unerupted permanent teeth and rarely deciduous teeth. They are usually solitary in their presentation. Multiple and bilateral dentigerous cysts are an extremely rare presentation in the absence of developmental syndromes or systemic diseases or the use of prescribed certain medications. We hereby present a case of a bilateral dentigerous cyst of the maxilla in a 10-year-old child involving the crowns of unerupted permanent second premolar on the right side and the unerupted permanent canine on the left side. An effort has also been made to review the existing literature on this entity and to stress the importance of radiographic and histopathological examinations in diagnosing such an entity.